2005
DOI: 10.1159/000084337
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Resistance in Patients with Obstructive Sleep Apnea

Abstract: The aim of this study was to investigate the relationship between the severity of obstructive sleep apnea (OSA) and nasal resistance (NR). Eighty-five consecutive patients were recruited owing to their symptoms indicating OSA. All patients received polysomnography and anterior rhinomanometry (performed during wakefulness in the supine position). Patients were divided into low and high NR groups according to their rhinomanometric results; their polysomnographic, anthropometric and demographic data were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Total NR was derived by the standard formula total NR = (right NR × left NR)/(right NR + left NR). Detailed procedures for anterior rhinomanometry have been published elsewhere 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total NR was derived by the standard formula total NR = (right NR × left NR)/(right NR + left NR). Detailed procedures for anterior rhinomanometry have been published elsewhere 14 …”
Section: Methodsmentioning
confidence: 99%
“…Detailed procedures for anterior rhinomanometry have been published elsewhere. 14 The acoustic rhinometry (AR) technique used in this study was conducted in the laboratory. A commercialized nasal probe consisting of rigid PVC tube 1.2 cm in internal diameter and 5 cm in length (RhinoSleep, Lynge, Denmark) was used to connect the AR instrument to the nasal alae.…”
Section: Nasal Measuresmentioning
confidence: 99%
“…No apparent previous reports in the literature of the effects of inhaled irritants that used anterior rhinomanometry were found. However, two groups studying the relationship between nasal resistance and obstructive sleep apnea reported that resistance in the most congested nostril correlated better with measures of apnea severity than bilateral nasal resistance (Li et al, 2005;Tagaya et al, 2010).…”
Section: Increases In Nasal Resistance In Rhinitic Subjectsmentioning
confidence: 99%
“…8,25,26 Contrary to these studies, there are also studies without any relation between nasal resistance and apnea hypopnea index (AHI). 9,27,28 In these studies, nasal resistance is measured in sitting position but Nakata et al showed that nasal resistance and AHI are correlated in supine position, whereas it is not detected on sitting position. 29 According to our findings, we did not detect any correlation between increased BMI and total expiratory and inspiratory nasal resistance.…”
Section: Discussionmentioning
confidence: 99%